Operationalizing the serviceshed concept to enhance the effectiveness and equity of flood regulation services in systematic conservation planning - Xue Ding; Jun-Long Huang; Yu Tao; Jiman Li; Henghui Xi; Weixin Ou (Environmental Impact Assessment Review, 2026)

A VvETC3-linked repressive layer mediates extracellular self-DNA–primed resistance to gray mold in postharvest grapes - Chunhong Li; Yijia Xia; Siyu Ou; Kejiang Chen; Fei Xiang; Kaituo Wang; Jun He; Minghua Zhou; Yonghua Zheng (Postharvest Biology and Technology, 2026)

Structural and physicochemical responses of seaweed-derived insoluble dietary fiber to temperature-controlled steam explosion: A case study on Porphyra haitanensis - Yujia Ou; Binhui Zhou; Yesong Wang; Tao Hong; Lijun Li; Zedong Jiang; Hui Ni; Jun Lu; Mingjing Zheng (Innovative Food Science & Emerging Technologies, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Improvement of physicochemical and functional properties and potential bioaccessibility of rare ginsenoside Rg3 loaded on modified porous cassava starch - Wen-ting Wang; Hui-min Guo; Sheng-yuan Guo; Wen-jun Ou; Fei Gao; Kai-mian Li; Li-zhen Zhang; Gui-xing Ren (Food Chemistry, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Electrochemical construction of Turing-patterned plasmonic MOF substrate for machine learning-assisted SERS analysis of volatile organic compounds - Weihui Ou; Kai Wu; Zhijian He; Junda Shen; Xuanhe Hu; Jiangtao Li; Rui Lang; Jian Lu; Jun He (Chemical Engineering Journal, 2026)

Research on the Adaptive Response Mechanism of Bacterial Infection in Triplophysa siluroides - Yuanliang Duan; Ya Liu; Jun Ou; Feiyang Li; Xiaoyun Wu; Jianshen Lai; Jian Zhou; Mingjiang Song (Fishes, 2026)
Triplophysa siluroides, a unique species of plateau fish, holds significant economic value. However, its natural population has sharply declined due to overfishing and the construction of water conservancy projects. Investigating the various conditions necessary for its growth is a crucial prerequisite for successful artificial breeding. This study used Edwardsiella tarda as the pathogenic bacterium to determine the median lethal concentration following infection of T. siluroides, as well as to examine changes in tissues, organs, and gene expression. The study found that dead T. siluroides displayed symptoms such as abdominal distension, fluid accumulation, and a reddened anus, and the median lethal concentration of E. tarda for T. siluroides was calculated to be 1.00 × 106 CFU/mL. Following infection with E. tarda, the liver, intestine, gills, spleen, and kidneys exhibited varying degrees of lesions. Transcriptome sequencing identified a total of 54,667 genes. Compared to the blank control group, 192 genes were downregulated and 125 genes were upregulated in T. siluroides infected with E. tarda. In contrast, after infection with the poly(I:C) viral mimic, 225 genes were downregulated and 436 genes were upregulated. This study determined the median lethal concentration of E. tarda for T. siluroides via intraperitoneal injection under laboratory conditions. The results may contribute to disease prevention and control in the breeding of T. siluroides, as well as inform future risk assessments of infection in aquaculture water bodies.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Bisphenol exposure during pregnancy and serum total bile acid levels across trimesters: single and combined effects in pregnant women from Guangxi Zhuang, China - Jun Liang; Yu Zou; Zican Mo; Lixiang Pang; Kaiqi Yang; Peng Tang; Qian Liao; Liujuan Ou; Junshang Wen; Wanhui Li; Huishen Huang; Xiaoqiang Qiu (Environmental Pollution, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Innovative self-evolution manipulation for constructing ultra-uniform rich copper vacancies Cu31S16/GeS2 heterojunction towards exceptional sodium storage - Liang Cao; Jun Zhao; Yushen Liu; Yiwei Xue; Yafu Wang; Hongbo Geng; Xing Ou; Qingyu Li (Chemical Engineering Journal, 2025)

Study on hydrogen storage properties of Ca atom modified γ-graphyne - Jun-wei Liu; Jia-cheng Li; Cai-he Fan; Ling Ou; Ying-zhe Zhang (Process Safety and Environmental Protection, 2025)

Research on dynamic characteristics of a tension-leg modular floating structure system under tendon failure - Yanwei Li; Conghao Qian; Nianxin Ren; Jun Yan; Zhe Zhang; Jinping Ou (Ocean Engineering, 2025)

Heterosis analysis of heat and cold tolerance in hybrid offspring of sea urchin Mesocentrotus nudus: Implications for breeding - Wenzhuo Tian; Xuechun Jiang; Hao Guo; Peng Liu; Tongshan Jia; Shuaichen Wu; Fanjiang Ou; Xiaofei Leng; Xuguang Li; Lijie Wang; Yaqing Chang; Weijie Zhang; et al. (Aquaculture International, 2025)

A multi-effect synergistic photo-therapy PAS/ICG-Cu@ZOL hydrogel dressing with enhancing adaptive immunomodulatory and antibiofilm properties for improved healing of diabetic infected wounds - Bibo Ren; Jun Li; Kang Dai; Jiale Li; Chao Hu; Shiyu Wang; Kaijun Li; Zelin Ou; Haibo Wang (Chemical Engineering Journal, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Copula-based joint impact assessment of rainfall and tidal level on flood risk in tidal-influenced plain river network areas, Taihu Lake Basin - Hong Zhou; Jun Liu; Cheng Gao; Weidong Li; Shufang Ou; Yi Zhou; Qinghua Luan (Journal of Hydrology, 2025)

Use of non-targeted metabolomics to explore metabolic differences between stem cells and callus of Tetraena mongolica - Yeru Yang; Haihua Li; Ruiping Wang; Jiahe Li; Ling Li; Jiayu Li; Lin Ou; Jun Li; Chengbo Zhang; Liyu Wang; Fengqiang Yu; Zhi He; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Machine learning-enhanced flavoromics: Identifying key aroma compounds and predicting sensory quality in sauce-flavor baijiu - Shuai Li; Yueran Han; Li Wang; Ya Zhang; Fan Wang; Youming Ou; Haoying Li; Liang Yang; Shuyi Qiu; Jun Lu (Food Chemistry, 2025)

Impact of agricultural straw open-field burning on concentrations of six criteria air pollutants in China - Hao-Neng Huang; Zhou Yang; Yuming Guo; Jia-Jun Ma; Bo-Wen Ming; Jun Yang; Cui Guo; Li Li; Chun-Quan Ou (Environmental Pollution, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Dynamic multi-objective evolutionary algorithm based on dual-layer collaborative prediction under multiple perspective - Yaru Hu; Yana Li; Junwei Ou; Jiankang Peng; Jun Li; Jinhua Zheng (Swarm and Evolutionary Computation, 2025)

Seasonal variations and hydrological management regulate nutrient transport in cascade damming: Insights from carbon and nitrogen isotopes - Yujing Yang; Wanfa Wang; Shengde Yu; Yuanbi Yi; Sen Xu; Yuanzhi Yao; Jun Zhong; Wenhong Shi; Sainan Chen; Qixin Wu; Zuhong Ou; Hu Ding; et al. (Water Research, 2025)

Fatigue analysis of monopile-supported offshore wind turbine under varied supported conditions - Jun Liang; Ying Wang; Chao Li; Jinping Ou (Ocean Engineering, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

An in-depth understanding of the role and mechanisms of T cells in immune organ aging and age-related diseases - Yudai Xu; Zijian Wang; Shumin Li; Jun Su; Lijuan Gao; Junwen Ou; Zhanyi Lin; Oscar Junhong Luo; Chanchan Xiao; Guobing Chen (Science China Life Sciences, 2025)

Heterosis of the interspecific sea urchin hybrids between Strongylocentrotus intermedius and Heliocidaris crassispina - Fanjiang Ou; Xiaofei Leng; Xuechun Jiang; Hao Guo; Peng Liu; Wenzhuo Tian; Xuguang Li; Lijie Wang; Jun Ding; Yaqing Chang; Weijie Zhang (Aquaculture, 2024)

Temperature differentially regulates estuarine microbial N2O production along a salinity gradient - Tie-Qiang Mao; Yong Zhang; Ya-Fei Ou; Xiao-Fei Li; Yan-Ling Zheng; Xia Liang; Min Liu; Li-Jun Hou; Hong-Po Dong (Water Research, 2024)

The IGD-based prediction strategy for dynamic multi-objective optimization - Yaru Hu; Jiankang Peng; Junwei Ou; Yana Li; Jinhua Zheng; Juan Zou; Shouyong Jiang; Shengxiang Yang; Jun Li (Swarm and Evolutionary Computation, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Origins of atmospheric nitrous acid and their contributions to OH radical from ship plumes, marine atmosphere, and continental air masses over South China Sea - Xue Ni; Cuizhi Sun; Zhenhao Ling; Yao Li; Yongyun Zhang; Hengjia Ou; Baoling Liang; Qibin Sun; Shixin Mai; Shengzhen Zhou; Jun Zhao (Science of The Total Environment, 2024)

SIZ1-mediated SUMOylation of CPSF100 promotes plant thermomorphogenesis by controlling alternative polyadenylation - Zhibo Yu; Jun Wang; Cheng Zhang; Qiuna Zhan; Leqian Shi; Bing Song; Danlu Han; Jieming Jiang; Junwen Huang; Xiaolin Ou; Zhonghui Zhang; Jianbin Lai; et al. (Molecular Plant, 2024)

Treatment of manganese and lead poisoning with sodium para-aminosalicylic acid: A contemporary update - Yu-Han Xie; Han-Xiao Song; Jian-Chao Peng; Shao-Jun Li; Shi-Yan Ou; Michael Aschner; Yue-Ming Jiang (Toxicology Letters, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Association between ambient temperature and mammalian-related injuries in Guangzhou, China, 2014–2019 - Jia-Jun Ma; Ze-Jie Xu; Boheng Liang; Zhou Yang; Li Li; Hao-Neng Huang; Bo-Wen Ming; Pengzhe Qin; Chun-Quan Ou (Science of The Total Environment, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Haze weather and mortality in China from 2014 to 2020: Definitions, vulnerability, and effect modification by haze characteristics - Zhou Yang; Jiangmei Liu; Jun Yang; Li Li; Ting Xiao; Maigeng Zhou; Chun-Quan Ou (Journal of Hazardous Materials, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Propofol modulates neural dynamics of thalamo-cortical system associated with anesthetic levels in rats - Xuliang Jiang; Xin Wen; Guoyao Ou; Shitong Li; Yali Chen; Jun Zhang; Zhenhu Liang (Cognitive Neurodynamics, 2023)

Integrated metabolomic and transcriptomic responses to heat stress in a high-altitude fish, Triplophysa siluroides - Yeyu Chen; Xiaoyun Wu; Pengcheng Li; Ya Liu; Mingjiang Song; Feiyang Li; Jun Ou; Jiansheng Lai (Fish & Shellfish Immunology, 2023)

Isolation and characterization of 73 SNP markers in Schizopygopsis chengi baoxingensis - Mingjiang Song; Yeyu Chen; Xiaoyun Wu; Ya Liu; Feiyang Li; Quan Gong; Jun Ou; Pengcheng Li; Qiaolin Zou; Jiansheng Lai (Conservation Genetics Resources, 2023)

Ultra-high output hybrid nanogenerator for self-powered smart mariculture monitoring and warning system - Liqiang Liu; Jun Li; Zhengxin Guan; Leilei Zhao; Zhiyu Tian; Shouchuang Jia; Hongxin Hong; Zeyu He; Haiyang Wen; Ruiyuan Huang; Hui Cui; Wei Ou-Yang; et al. (Chemical Engineering Journal, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Evaluating the ecological vulnerability of Chongqing using deep learning - Jun-Yi Wu; Hong Liu; Tong Li; Yuan Ou-Yang; Jing-Hua Zhang; Teng-Jiao Zhang; Yong Huang; Wen-Long Gao; Lu Shao (Environmental Science and Pollution Research, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Study on the Bottom-Hole Rock-Breaking Law of Electrohydraulic Shockwave - Kerou Liu; Hui Zhang; Jun Li; Kuangsheng Zhang; Yangyong Ou; Yufei Chen; Xinrui Wang; Zhixiang Cai (Rock Mechanics and Rock Engineering, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Large-scale mariculture of the sponge Haliclona simulans on floating rafts in Zhao'an Bay, Fujian Province, China - Zhunfei Li; Guangyuan Xia; Huilong Ou; Ming Chen; Yingzhe You; Jun Chen (Aquaculture, 2023)

Numerical investigation of wave run-up and load on heaving cylinder subjected to regular waves - Xinlong Wang; Dongsheng Qiao; Linxiao Jin; Jun Yan; Bin Wang; Binbin Li; Jinping Ou (Ocean Engineering, 2023)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Therapeutic Effects of Sodium Para-Aminosalicylic Acid on Cognitive Deficits and Activated ERK1/2-p90RSK/NF-κB Inflammatory Pathway in Pb-Exposed Rats - Li-li Lu; Yu-wen Zhang; Zhao-cong Li; Yuan-yuan Fang; Lei-lei Wang; Yue-song Zhao; Shao-jun Li; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2022)

Four new prenylflavonol glycosides from the leaves of Cyclocarya paliurus - Zi-Jun Ye; Hui-Hui Sun; Zu-Hui Chen; Jian-Ping Wu; Jing Li; Hui Zhu; Lu-Lu Huang; Xi-Wen Chang; Sai-Yu Ou; Wen-Xuan Wang; Xiao-Ai He; Gang-Zhi Zhu; et al. (Natural Product Research, 2022)

Simulation and test of the movement process of mixed flow composed of slurry and coarse particle - Xian-jun Ji; Ying Liang; Guo-qiang Ou; Hua-li Pan (European Journal of Environmental and Civil Engineering, 2021)

Characteristics of soil erosion and sediment size distribution for different land uses in the Chinese Mollisol region - Hai-ou Shen; Jun Feng; Dong-li Wang; Hong-li Li; Yu Wang (Journal of Mountain Science, 2021)

Effects of hourly levels of ambient air pollution on ambulance emergency call-outs in Shenzhen, China - Ting-Ting Chen; Zhi-Ying Zhan; Yi-Min Yu; Li-Jun Xu; Ying Guan; Chun-Quan Ou (Environmental Science and Pollution Research, 2020)

An ecological barrier between the Himalayas and the Hengduan Mountains maintains the disjunct distribution of Roscoea - De‐Bao Li; Xiao‐Kun Ou; Jian‐Li Zhao; Qing‐Jun Li (Journal of Biogeography, 2020)
Aim Regional disjunction in mountainous regions is ubiquitous and is closely associated with the evolution of mountain biodiversity. However, the mechanisms of maintaining regional disjunction are often ignored, especially regarding the role of ecological barriers. The aim of this study is to test whether an ecological barrier maintains the regional disjunction of Roscoea between the Himalayas (HIM) and the Hengduan Mountains/Yun‐Gui Plateau (HMY). Location The Himalayas and the Hengduan Mountains/Yun‐Gui Plateau, Asia. Taxon Monocot:Zingiberales:Zingiberaceae: Roscoea . Methods Occurrence data from Roscoea were collected from public databases and field investigations. Environmental niche modelling (ENM) was used to predict the potential distribution of Roscoea during the Last Interglacial (LIG), the Last Glacial Maximum (LGM), the present and the future. An environmental variable difference test, principal component analysis (PCA), discriminant function analysis (DFA) and niche identity test were employed to qualify and quantify the contributions of environmental factors to ecological divergence based on 7 and 26 environmental variables. Results Environmental niche modelling predicted an ecological gap of Roscoea between the HIM and the HMY from the LIG into the future, excluding the LGM. Statistically significant differences were detected in eight unique environmental variables across the Gap, which was mostly related to low temperatures and high moisture levels. The PCA, DFA and niche identity test suggested larger ecological separations among the Gap, the HIM and the HMY based on 26 environmental variables than based on seven variables. Main conclusions All clues point to an ecological barrier that has been maintaining the regional disjunction of Roscoea . This ecological barrier is predicted to be stable under future climate change and may reflect long‐term ecological divergence shaped by the adaptation of Roscoea to divergent habitats. Our study highlights that the effects of specific environmental variables, with possible interactions among multiple ecological factors, being closely related to the ecological barrier.

Long runout mechanism of the Shenzhen 2015 landslide: insights from a two-phase flow viewpoint - Cheng Qiao; Guo-qiang Ou; Hua-li Pan; Chao-jun Ouyang; Yang Jia (Journal of Mountain Science, 2018)

Identification of the dwarf gene GmDW1 in soybean (Glycine max L.) by combining mapping-by-sequencing and linkage analysis - Zhong-feng Li; Yong Guo; Lin Ou; Huilong Hong; Jun Wang; Zhang-xiong Liu; Bingfu Guo; Lijuan Zhang; Lijuan Qiu (Theoretical and Applied Genetics, 2018)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Functional polymorphisms in the gene encoding macrophage migration inhibitory factor (MIF) are associated with active pulmonary tuberculosis - Shou-Gang Kuai; Qin-Fang Ou; De-Hong You; Zhong-Bo Shang; Jun Wang; Jun Liu; Xi-Ke Zhou; Hao Pei; Li-Hua Huang (Infectious Diseases, 2016)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

SecReT6 : a web‐based resource for type VI secretion systems found in bacteria - Jun Li; Yufeng Yao; H. Howard Xu; Limin Hao; Zixin Deng; Kumar Rajakumar; Hong‐Yu Ou (Environmental Microbiology, 2015)
Summary SecReT6 ( http://db‐mml.sjtu.edu.cn/SecReT6/ ) is an integrated database providing comprehensive information on type VI secretion systems ( T6SSs ) in bacteria. T6SSs are a class of sophisticated cell contact‐dependent apparatuses involved in mediating antagonistic or synergistic communications between bacteria and/or bacteria and eukaryotes. These apparatuses have recently been found to be widely distributed among G ram‐negative bacterial species. SecReT6 offers a unique, readily explorable archive of known and putative T6SSs , and cognate effectors found in bacteria. It currently contains data on 11 167 core T6SS components mapping to 906 T6SSs found in 498 bacterial strains representing 240 species, as well as a collection of over 600 directly relevant references. Also collated and archived were 1340 diverse candidate secreted effectors which were experimentally shown and/or predicted to be delivered by T6SSs into target eukaryotic and/or prokaryotic cells as well as 196 immunity proteins. A broad range of T6SS gene cluster detection and comparative analysis tools are readily accessible via SecReT6 , which may aid identification of effectors and immunity proteins around the T6SS core components. This database will be regularly updated to ensure its ongoing maximal utility and relevance to the scientific research community.

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

Debris flow formation process and critical hydrodynamic conditions in the meizoseismal area of the Wenchuan earthquake - Jun Wang; Yan Yu; Hua-li Pan; Cheng Qiao; Guo-qiang Ou (Journal of Mountain Science, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Impact of Megacity Shanghai on the Urban Heat-Island Effects over the Downstream City Kunshan - Han-Qing Kang; Bin Zhu; Tong Zhu; Jia-Li Sun; Jian-Jun Ou (Boundary-Layer Meteorology, 2014)

Fruit and vegetable intake and the risk of colorectal cancer: results from the Shanghai Men’s Health Study - Emily Vogtmann; Yong-Bing Xiang; Hong-Lan Li; Emily B. Levitan; Gong Yang; John W. Waterbor; Jing Gao; Hui Cai; Li Xie; Qi-Jun Wu; Bin Zhang; Yu-Tang Gao; et al. (Cancer Causes & Control, 2013)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Lanthanide Salts of Heteropoly Molybdotungstosilicate LnHSiMo10W2O40·xH2O (Ln = Pr, Nd, Sm, Gd, Tb, Dy, Yb) Binding to Bovine Serum Albumin: A Fluorescence Quenching Study - Ai-Min Bai; Yu Ou-Yang; Hua-Li Yue; Xiao-Ling Li; Yan-Jun Hu (Biological Trace Element Research, 2012)

Determination of the specific interaction between palmatine and bovine serum albumin - Yu Ou-Yang; Xiao-Ling Li; Hong Wang; Min Fang; Yan-Jun Hu (Molecular Biology Reports, 2012)

Effects of SCR-3 on the immunosuppression accompanied with the systemic inflammatory response syndrome - Jun Li; Jie Niu; Shan Ou; Zhan-Yong Ye; Deng-Qun Liu; Feng-Chao Wang; Yong-Ping Su; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Inhibitory effect of celecoxib in lung carcinoma by regulation of cyclooxygenase-2/cytosolic phospholipase A2 and peroxisome proliferator-activated receptor gamma - Ming Zhang; Zhi-Gang Xu; Zhuo Shi; Dan Shao; Ou Li; Wei Li; Zhi-Jun Li; Kai-Zhong Wang; Li Chen (Molecular and Cellular Biochemistry, 2011)

Systematic analysis of potato acid invertase genes reveals that a cold-responsive member, StvacINV1, regulates cold-induced sweetening of tubers - Xun Liu; Chi Zhang; Yongbin Ou; Yuan Lin; Botao Song; Conghua Xie; Jun Liu; Xiu-Qing Li (Molecular Genetics and Genomics, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)